Importance of Collateralization in Patients With Large Artery Intracranial Occlusive Disease: Long-Term Longitudinal Assessment of Cerebral Hemodynamic Function - McKetton, Larissa; Venkatraghavan, Lakshmikumar; Poublanc, Julien; Sobczyk, Olivia; Crawley, Adrian P.; Rosen, Casey; Silver, Frank L.; Duffin, James; Fisher, Joseph A.; Mikulis, David J. (Frontiers in Neurology, 2018)
Patients with large artery intracranial occlusive disease (LAICOD) are at risk for both acute ischemia and chronic hypoperfusion. Collateral circulation plays an important role in prognosis, and imaging plays an essential role in diagnosis, treatment planning, and prognosis of patients with LAICOD. In addition to standard structural imaging, assessment of cerebral hemodynamic function is important to determine the adequacy of collateral supply. Among the currently available methods of assessment of cerebral hemodynamic function, measurement of cerebrovascular reactivity (CVR) using BOLD MRI and precisely controlled CO2 has shown to be a safe, reliable, reproducible and clinically useful method for long-term assessment of patients. Here we report a case of long-term follow-up in a 28-year-old Caucasian female presented to the neurology clinic with a history of TIA’s and LAICOD of the right middle cerebral artery (MCA). Initial structural MRI showed a right MCA stenosis and a small right coronal radiate lacunar infarct. Her CVR study showed a large area of impaired CVR with a paradoxical decrease in BOLD signal with hypercapnia involving the right MCA territory indicating intra-cerebral steal. The patient was managed medically with anticoagulant and antiplatelet therapy and was followed up for over 9 years with both structural and functional imaging. Cortical thickness measures were longitudinally assessed from a region of interest that was applied to subsequent time-points in the cortical region exhibiting steal physiology and in the same region of the contralateral healthy hemisphere. In the long-term follow-up, the patient exhibited improvement in her CVR as demonstrated by the development of collaterals with negligible changes to cortical thickness. Management of patients with LAICOD remains challenging since no revascularization strategies have shown efficacy except in patients with moyamoya disease. Management is well defined for acute ischemia where the presence and the adequacy of the collateralization dictate the need for intervention. Long-term assessment in neurovascular uncoupling (i.e., chronic ischemia) may reveal improvements in CVR as the durability of compensatory collaterals improve, even in cases with no intervention. Thus, assessment of cerebrovascular hemodynamics using CVR measurements coupled with time-of-flight MR angiograms can be useful in the clinical management of patients with LAICOD.